The use of playfulness as a resource in the teaching-learning process - ARAUJO, Luana Valentim (2023)
This article is the result of research that aims to analyze how the use of play has been developed in the educational context and to identify whether it helps to motivate students, taking into account the perspective of teachers and students, through articles that collected data, such as: questionnaires, interviews and case studies. Therefore, bibliographic searches were carried out so that we could find research that answered questions about this tool. 07 articles were selected for analysis, using the keywords (Ludico, Ensino-Aprendizagem and Motivação), in the following databases: Portal de Periódicos da CAPES and Google Scholar. The themes appear in different ways, however, it was necessary to read and interpret each one. The searches through the keywords were made in Portuguese, to understand how this situation occurs in our country. Research shows us that playing is a very important tool and influences student learning and motivation.